INVOLVEMENT AND FORMATION OF PARISH PASTORAL COUNCIL OFFICERS IN THE EASTERN VICARIATE OF THE ARCHDIOCESE OF CAPIZ - Anoche, Menard Amongo (President University, 2025)
The church is facing challenges due to the growing secularization of society, leading to a decline in religious influence and participation. The Parish Pastoral Council plays a vital role in the Catholic Church, assisting the priest in fostering an active and enthusiastic parish community. The council's effectiveness depends on active involvement and quality formation from the parish. The study aimed to assess the level of involvement in doctrine, worship, and values, as well as the extent of formation in didache (teachings), koinonia (community), and diakonia (service) of 180 randomly selected parish pastoral council officers in the Eastern Vicariates of the Archdiocese of Capiz. A validated and reliability-tested researcher-made questionnaire was used to gather the data on the socio-demographic profile of the respondents; the level of involvement and the extent of formation of parish pastoral council officers. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, t-test, ANOVA, and Pearson-r. Utilizing the quantitative research design, the results revealed that the level of involvement and the extent of formation of the parish pastoral council officers was “high